Antibiotic therapy of gastrointestinal infections - Albrecht, Piotr; Kotowska, Maria (Przewodnik Lekarza/Guide for GPs, 2007)
In these paper the principles of rational antibiotic therapy for H. pylori , acute gastroenterocolitis, traveller’s diarrhoea, pseudomembranous colitis, bacterial overgrowth of the intestine, IBS, Crohn’s disease and perianal abscess are presented.